Trophic transfer of microplastics in Phalacrocorax auritus (Double-Crested Cormorants) and fish in Lake Champlain - Bullis, Kathleen; Stewart, James; Walrath, Joshua; Putnam, Alexandra; Hammer, Chad; VanBrocklin, Hope; Buska, Brandon; Clune, Alexis; Garneau, Danielle (2018)
The goal of this research was to determine whether microplastics (MP) result in trophic transfer within invertebrates, fish, and Phalacrocorax auritus (Double-crested Cormorants) resident to Lake Champlain. We did so by quantifying and characterizing (e.g., fragment, fiber, film, foam, pellet) plastic particulate. Wet peroxide oxidation digests were performed on digestive tracts of 665 lake organisms, specifically invertebrates, 15 species of fish, Salvenlius namaycush (Lake Trout), Micropetrus salmoides (Largemouth Bass), Esox lucius (Northern Pike), Amia calva (Bowfin), Micropterus dolomieu (Smallmouth Bass), Salmo salar (Atlantic Salmon), Ameiurus nebulosus (Brown Bullhead Catfish), Perca flavescens (Yellow Perch), Archosargus probatocephalus (Sheepshead), Morone americana (White Perch), Lepomis macrochirus (Bluegill sunfish), Osmerus mordax (Rainbow Smelt), Cottus cognatus (Slimy Sculpin), Ambloplites rupestris (Rock Bass), Alosa pseudoharengus (Alewife), and Phalacrocorax auritis (Double-crested Cormorants). Our research indicated that fibers were the were the most common (80.1%) type of particulate found in all organisms, followed by fragments (9.64%), films (6.36%), foam (3.01%), and pellets (<1%). The fish species Amia calva (Bowfin) contained the greatest average number of plastic particulate (χ ̅= 29.67), followed by Salvelinus hamaycush (Lake Trout) (χ ̅= 22), and Esox Lucius (Northern Pike) (χ ̅= 18.42). Among digested fish, stomachs contained the greatest mean number of MPs (χ ̅= 5.84), followed by the esophagus (χ ̅= 5.48) and intestines (χ ̅=4.76). These findings illustrate trophic transfer in addition to direct consumption of MP’s in Lake Champlain organisms, as invertebrates, fish, and double-crested cormorants contained on average 0.615, 6.49, and 22.93 microplastic particles. Results from this research serve to inform residents of the Lake Champlain watershed, anglers, non-profit lake organizations, as well as public health and government officials of the risks microplastics pose to aquatic ...